Platform Ideologies: Ideological Production in Digital Intermediation Platforms and Structural Effectivity in the "Sharing Economy". (January 2020) - Karatzogianni, Athina; Matthews, Jacob
Drawing from three sets of literature (critical economy of platformization, labor organization, and digital activism), this article introduces an integrated framework to analyze ideological production in digital intermediation platforms, particularly in relation to the sharing economy. We analyze documents, fieldwork interviews from twenty-eight actors, and observation of events in Barcelona, Paris, and Berlin during 2015–2017. We find that there are three dominant ideological strands: "sharing economy, " "commons, " and "platform cooperativism, " within a spectrum that ranges from legitimizing neoliberalism and/or reasserting a reformist, more humane capitalism to more radical visions: cooperative society to commons-oriented production, and resisting privatization, through the recapturing of public space as commons. The actors we interviewed can be seen as part of an intermediate class, dependent on platforms for their survival, and who end up involuntary promoters of their own alienation and exploitation, consolidating the deterioration of the very digital labor conditions they seek to transform.